Synthesis and primary screening of the antioxidant activity of some 4-thioxo- and 4-imino- thiazolidin-2-ones - Z. І. Сhulovska; І. V. Drapak; T. I. Chaban; V. S. Matiychuk; I. G. Chaban; V. V. Ogurtsov (The State Expert Center of the Ministry of Health of Ukraine, 2021)
As a result of metabolic transformations of substances in the human body in the reactions of lipid peroxidation, reactive oxygen species are formed. Normally, the regulation of the production of activated oxygen metabolites and free radicals in human tissues and organs is carried out by the antioxidant system. Despite its high efficiency, antioxidant system it is not always to protect the human body from the development of oxidative stress. Thiazolidinones are among the most intensively studied heterocyclic systems, since they possess a wide spectrum of biological activity. Based on the above, the synthesis of some 4-thioxo- and 4-iminothiazolidin-2-ones and the study of their antioxidant activity is an topical direction. The aim of our work was to synthesize some C5 substituted derivatives of 4-thioxothiazolidin-2-one and 4-iminothiazolidin-2-one, as well as to conduct a primary screening of their antioxidant activity. The objects of study were C5 substituted 4-thioxo- and 4-iminothiazolidin-2-ones. The composition and structure of the synthesized compounds were confirmed by the data of elemental analysis and 1H NMR spectroscopy. The antioxidant activity of the synthesized compounds was studied in vitro, determining the decrease in the concentration of free radicals. The synthesis of 12 derivatives of 4-thioxothiazolidin-2-one and 4-iminothiazolidin-2-one was carried out. These substances are obtained by structural modification to the C5 position of the base scaffolds. The antioxidant activity of the synthesized compounds was measured in vitro by the method of scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. Ascorbic acid was used as a standard. As a result of screening, 2 highly active compounds with a pronounced antioxidant effect were identified. As a result of structural modification of the basic scafolds, 12 corresponding C5 substituted thiazolidinones were obtained. During the primary pharmacological screening of antioxidant activity, 2 substances with a pronounced antioxidant effect were isolated. Further optimization of the structure is currently in progress.